Tilapia male urinary pheromone stimulates female reproductive axis - Huertas, Mar (2014)
Mozambique tilapia males congregate in leks where they establish dominance hierarchies and attract females to spawn in sandy pits. Dominant males store more urine than subordinates and the pattern of urination and the high sensitivity of females to male urine suggest chemical signalling via the urine. Here we show that pre-ovulated and post-spawn females when exposed to dominant male urine increased significantly, in less than 1 h, the release rate of the maturation-inducing steroid 17,20bdihydroxypregn- 4-en-3-one which is maintained elevated for at least 6 h. This indicates a pheromonal role for male urine in the synchronisation of spawning. Furthermore, we show that the lack of affinity of 17,20bP to sex steroid binding globulin explains, at least partly, its rapid release and lack of detection in the blood. Thus tilapia urine involvement in several communication processes confirms that cichlids have evolved a sophisticated chemical signalling system together with their complex visual, acoustic and behavioural displays.